Triple X syndrome and various abnormality of 3q in Iraqi women: a case report - Ismail, Noor H. (Iraqi Journal of Cancer and Medical Genetics, 2014)
Triple X syndrome 47XXX is a sex chromosome abnormality characterized by presence of an extra X chromosome. Most of the girls born with triple X chromosomes have no signs or symptoms at birth. The condition often remains undiagnosed until adulthood when the genetic defect is discovered on investigation for other reasons as in this case of a 52 year old lady who diagnosed with systemic lupus erythematosus (SLE). The chromosomal analysis for peripheral blood cells by using Gbanding technique revealed trisomy X and various abnormality of 3q karyotype. Chromosomal analysis was also done for two daughters and one son of the patient that showed normal karyotype. In conclusion our findings provide additional support for the hypothesis that X-chromosome polysomy may confer increased susceptibility to SLE. The association of SLE with chromosomal abnormality of 3q found in our patient needs further studies to uncover the role of genes affected by this aberration in SLE.